2007
DOI: 10.1021/ma070807c
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film Thickness Gradients and Spatial Patterning via Salt Etching of Polyelectrolyte Multilayers

Abstract: We demonstrate the time- and concentration-dependent dissolution (etching) of polyelectrolyte multilayer (PEM) films comprised of poly(allylamine hydrochloride) (PAH) and poly(acrylic acid) (PAA) immersed in NaCl solutions. PEM thickness decreases to a reproducible unchanging value that depends upon the initial film thickness and the concentration of NaCl. As opposed to a “top-down” removal of PEM chains from the film, the dissolution mechanism involves the diffusion and association of chains throughout the PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 39 publications
3
62
0
1
Order By: Relevance
“…The presence of the charged substrate helps keep the remaining layers together, while amide hydrolysis slowly proceeds to degrade the remaining films. Similar salt-induced deconstruction has been reported previously by Ren et al and Schüler and Caruso for DNA-containing multilayers [46,47] and others [48][49][50], although mostly at higher salt concentrations than 0.15 M utilized in this study.…”
Section: Dna Release Profiles Under Physiological Conditionssupporting
confidence: 91%
“…The presence of the charged substrate helps keep the remaining layers together, while amide hydrolysis slowly proceeds to degrade the remaining films. Similar salt-induced deconstruction has been reported previously by Ren et al and Schüler and Caruso for DNA-containing multilayers [46,47] and others [48][49][50], although mostly at higher salt concentrations than 0.15 M utilized in this study.…”
Section: Dna Release Profiles Under Physiological Conditionssupporting
confidence: 91%
“…It makes it possible to adjust film degradability by controlling salt concentrations. Cohen and co-workers [58] have reported this phenomenon in (PAA/PAH) films and made a proof of concept by forming a thickness gradient using this method. Such gradients could prove to be useful in the study of cell processes, as discussed in Section 5 of this review.…”
Section: Charge Matchingmentioning
confidence: 87%
“…Upon exposure of a multilayer to a 10 mm solution of PPh 3 , a stronger base and a tighter coordinating ligand for the Pd II complexes along PNBE + , the absorbance intensity decreased dramatically within a few minutes (Figure 1 B), thus demonstrating the removal of our multilayers and suggesting another possible trigger mechanism for top-down patterning. [22] In summary, we have demonstrated that coordination chemistry between polymer-supported palladium complexes and polymeric bases can be used to assemble CoPMs. The CoPMs produced in this fashion rival the stability of covalent multilayers in the solid state and most organic solvents, while retaining the responsiveness of PEMs, thus adding a new surface functionalization method with unique properties to surface scientists "toolbox".…”
mentioning
confidence: 86%